An RNA-based toolbox to advance cellular computing.
Scientists from Germany, France and Austria have successfully programmed cellular networks and community behaviour of bacteria using newly engineered 'RNA based devices' (RNAdevs)-small molecular modules that regulate gene expression and function mainly based on ribonucleic acid sequences. The resulting toolbox opens the door to various applications in white biotechnology and medicine.